Effects of Protein, Calcium, and pH on Gene Transcription, Cell-Envelope Peptidase Activity of Lactococcus lactis Strains, and the Formation of Bitter Peptides - Forler, Benjamin (Foods, 2021)
Calcium- and protein-rich fermented milk products, such as concentrated yoghurts and fresh cheeses, may contain undesired bitter peptides, which are generated by the proteolytic cleavage of casein. Up to now, it is not clear whether this process is caused by endogenous milk enzymes, such as plasmin and cathepsin D, or whether proteolytic enzymes from applied starter cultures, such as the lactococcal cell-envelope peptidase PrtP, are involved. A sensory analysis of fresh cheese products made from milk concentrates fermented with prtP-negative and -positive Lactococcus lactis strains revealed bitterness in the products fermented with prtP-positive L. lactis strains. Two prtP-positive strains, LTH 7122 and LTH 7123, were selected to investigate the effect of increased calcium concentrations (additional 5 mM and 50 mM CaCl(2)) at neutral (pH 6.6) and acidic (pH 5.5) pH-values on the transcription of the prtP gene and its corresponding PrtP peptidase activity in milk citrate broth (MCB). For both strains, it was shown that prtP transcription was upregulated only under slightly elevated calcium conditions (5 mM CaCl(2)) after 5 h of growth. In concordance with these findings, PrtP peptidase activity also increased. When higher concentrations of calcium were used (50 mM), prtP expression of both strains decreased strongly by more than 50%. Moreover, PrtP peptidase activity of strain LTH 7123 decreased by 15%, but enzymatic activity of strain LTH 7122 increased slightly during growth under elevated calcium concentrations (50 mM CaCl(2)). Fermentations of reconstituted casein medium with 3.4% (w/v) and 8.5% (w/v) protein and different calcium concentrations using strain LTH 7122 revealed no clear relationship between prtP transcription and calcium or protein concentration. However, an increase in PrtP peptidase activity under elevated protein and calcium conditions was observed. The activity increase was accompanied by increased levels of bitter peptides derived from different casein fractions. These findings could be a possible explanation for the bitterness in fermented milk concentrates that was detected by a trained bitter panel.